Nano-cryospray: An adjuvant assisted approach to increase the efficacy of cryospray - Srivastava P.; Kumar A. (My University, 2025)
The present study proposes a novel approach to treat skin cancer. It is an amalgamation of two techniques; (i) Cryospray in which necrosis is achieved through local application of liquid nitrogen spray on lesions (occurring on superficial skin) and (ii) Transdermal Drug Delivery systems (TDDS) in which drugs are administered through the superficial skin. It focuses on increasing the cryoablation through the administration of nanoparticles in the skin. Biodegradable Magnesium Oxide (MgO) nanoparticles are selected to make nano-phantom. TEM and XRD results reveal the crystalline nature of MgO nanoparticle with particle diameter 10–40 nm. A comparative study of cryoablation is carried out between the nano-phantom and the normal-phantom while spraying liquid nitrogen through a commercial 0.8 mm diameter single hole nozzle. Quantitative and qualitative improvements in cryoablation are observed due to the presence of nanoparticle. Necrotic zone in nano-phantom is twice larger than in the normal-phantom up to an axial depth of 2 mm from the centre of spray for the same spraying distance. Minimum spraying distance for nano-phantom is estimated to be 13 mm. Among the three spraying distances selected for the study, it has been observed that cryoablation decreases as the spraying distance increases. The proposed approach can be used to enhance the scope of cryospray in the treatment of larger lesions like Squamous cell carcinoma, keloids etc. without incorporating the device modifications. © 2022 Elsevier Inc.